2013
DOI: 10.1186/alzrt219
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin levels in blood cells as a potential biomarker of Alzheimer’s disease

Abstract: IntroductionThe clinical features of Alzheimer’s disease (AD) overlap with a number of other dementias and conclusive diagnosis is only achieved at autopsy. Accurate in-life diagnosis requires finding biomarkers suitable for early diagnosis, as well as for discrimination from other types of dementia. Mounting evidence suggests that AD-dependent processes may also affect peripheral cells. We previously reported that calmodulin (CaM) signaling is impaired in AD lymphoblasts. Here, we address the issue as to whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…46,[52][53][54] For this reason, peripheral cells, such as fibroblasts or blood lymphocytes, have been used extensively in the search for useful biomarkers that may correlate with expression and/or progression of disease. [55][56][57][58] In this regard, it has been shown that peripheral cells from patients with neurodegenerative disorders display cell cycle disturbances, 45,[59][60][61][62] reflecting the unscheduled cell cycle re-entry of postmitotic neurons and leading to apoptotic cell death. [63][64][65] The present work was undertaken to elucidate possible mechanisms involved in the PGRN deficiencyinduced WNT5A expression and signalling in PGRNdeficient lymphoblasts from patients with FTLD-TDP that were considered responsible for the increased activation of the CDK6/pRb-mediated cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…46,[52][53][54] For this reason, peripheral cells, such as fibroblasts or blood lymphocytes, have been used extensively in the search for useful biomarkers that may correlate with expression and/or progression of disease. [55][56][57][58] In this regard, it has been shown that peripheral cells from patients with neurodegenerative disorders display cell cycle disturbances, 45,[59][60][61][62] reflecting the unscheduled cell cycle re-entry of postmitotic neurons and leading to apoptotic cell death. [63][64][65] The present work was undertaken to elucidate possible mechanisms involved in the PGRN deficiencyinduced WNT5A expression and signalling in PGRNdeficient lymphoblasts from patients with FTLD-TDP that were considered responsible for the increased activation of the CDK6/pRb-mediated cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that Ec-CaM transcript expression showed a significant increase following the vibrio challenge, which may respond to the bacterial stimulation and neutralize the adverse effects of the vibrio invasion. In mammal, CaM signaling is impaired in lymphoblast of Alzheimer's disease, thus CaM level in blood cells can be regarded as a potential biomarker of Alzheimer's disease (Esteras et al 2013). Recent studies indicate that CaM is also considered as one of the most promising molecular indicators in teleost exposed to the chronic stressors (Alves et al 2010).…”
Section: Discussionmentioning
confidence: 97%
“…The affinities of S100B and calmodulin to IL-11 [(6.1 ± 1.6) 9 10 -6 M and (1.9 ± 0.3) 9 10 -5 M, respectively] are insufficient for their interaction with IL-11 in blood, since plasma concentrations of S100B, calmodulin, and IL-11 are within dozens of picomoles [39,53,54]. Meanwhile, high intracellular concentrations of calmodulin and S100B (up to dozens of micromoles [55,56]), NCS-1 (micromoles in the nervous system [57]), Cell Biochem Biophys and GCAP-1/2 (micromoles [58]) open up the possibility of their local interaction with extracellular IL-11 in processes accompanied by the disintegration of plasma membrane and efflux of cellular contents into the extracellular space.…”
Section: Interactions Of Il-11 With Calcium-binding Proteinsmentioning
confidence: 99%